BIO 300, a nanosuspension of genistein, mitigates pneumonitis/fibrosis following high‐dose radiation exposure in the C57L/J murine model. (3rd November 2017) - Jackson, Isabel L; Zodda, Andrew; Gurung, Ganga; Pavlovic, Radmila; Kaytor, Michael D; Kuskowski, Michael A; Vujaskovic, Zeljko
Abstract : Background and Purpose: BIO 300 nanosuspension (Humanetics Corporation) is being developed as a medical countermeasure (MCM) for the mitigation of the delayed effects of acute radiation exposure, specifically pneumonitis and fibrosis of the lung. The objective of this study was to determine the best dose and treatment duration of BIO 300 to mitigate lung injury and improve the likelihood for survival in C57L/J mice exposed to whole thorax lung irradiation (WTLI). Experimental Approach: Age‐ and sex‐matched C57L/J mice received a single dose of 11.0 or 12.5 Gy WTLI. BIO 300 (200 or 400 mg·kg −1, oral gavage) was administered daily starting 24 h post‐exposure for a duration of 2, 4, 6 or, in some cases, 10 weeks. Non‐treated controls were included for comparison in both sexes. Animals were observed daily for signs of major morbidity. Respiratory function was assessed biweekly. Lungs were collected, weighed and paraffin embedded for histological evaluation post mortem . Key Results: BIO 300 administered at an oral dose of 400 mg·kg −1 for 4 to 6 weeks starting 24 h post‐WTLI reduced morbidity associated with WTLI. The improvement in survival correlated with reduced respiratory frequency and enhanced pause. The irradiated lungs of mice treated with BIO 300 (400 mg·kg −1 ) for 4 to 6 weeks displayed less morphological damage and airway loss due to oedema, congestion and fibrotic scarring than the untreated, irradiated controls. Conclusions and Implications: BIO 300 is a promising MCM candidate to mitigate pneumonitis/fibrosis when administered daily for 4–6 weeks starting 24 h post‐exposure.